A shared respite—The meaning of place for family well-being in families living with chronic illness. Issue 1 (1st January 2016) - Årestedt, Liselott; Benzein, Eva; Persson, Carina; RÄmgÅrd, Margareta
Abstract : Living with chronic illness is a family affair that involves ongoing changes and challenges in everyday life. When life changes, the environment is important for family health and well-being. The relation between a place and a family is rarely described, and therefore the aim of this study was to explore the meaning of place for family well-being in families living with chronic illness. A qualitative design was chosen. Data were collected by photovoice combined with narrative family research interviews with 10 families living with chronic illness. A phenomenological hermeneutic analysis was used to interpret the data. The results showed that the meaning of place for family well-being in families living with chronic illness can be described as "a shared respite." This main theme included three subthemes: "a place for relief, " "a place for reflection, " and "a place for re-creation." These results were further understood by means of the concept place security. Feeling well means having place security in these families. Through knowledge about the meaning of place for family well-being, health care personnel can stimulate families living with chronic illness to find respite in places that contribute to well-being, both in familiar and new places.